Optimization of transdermal patch on parameters of composites of hyaluronic acid and zinc oxide nano particle filler - Dada, Kolawole S. (Вестник Томского государственного университета. Химия)
Transdermal drug delivery has gained popularity as a non-invasive method for controlled drug release compared to traditional delivery routes. Transdermal patches have emerged as a promising platform for delivering a variety of drugs due to their ease of use. The objective of this research was to create and characterize transdermal patches using various compositions and ratios of hyaluronic acid and zinc oxide nanoparticles. A micro molding technique was utilized to fabricate the patches which were subsequently characterized using Optical microscopy, FTIR, TGA and tensile strength testing. The study found that the mechanical strength and dissolution properties of the patches were influenced by the hyaluronic acid and zinc oxide nanoparticle ratios used in the fabrication process. Moreover, the patches demonstrated controlled filler dispersion in the polymer matrix as a function of the concentration of each filler. The results suggest that transdermal patches can be tailored to meet specific requirements for drug delivery applications using different compositions and ratios of hyaluronic acid and zinc oxide nanoparticles. This development has the potential to improve treatment outcomes and patient compliance in various therapeutic areas.